Update on Assessment of Estimated Glomerular Filtration Rate in Patients with Cirrhosis - Muhammad, Syed Akhter; Usman, Muhammad; Naseer, Muhammad; Azam, Muhammad; Mohkumuddin, Syed; Abdul Malik (Indus Journal of Bioscience Research, 2025)
Background: cirrhosis causes muscle loss and changes in creatinine levels, it is difficult to assess renal function in these patients. Often, creatinine-based processes calculate GFR too high which causes renal diseases to be diagnosed late and the illness to be undertreated. Objectives: To study which eGFR equation works best in cirrhotic patients and can most reliably be used in assessing and detecting early kidney impairment. Study Design: A Cross-Sectional Study. Place and Duration of study: From May 2024 to December 2024 Nephrology & Gastroenterology Department, Sandeman Provincial Hospital / Bolan Medical College / Hospital, Quetta. Methods: This cross-sectional study was performed at Nephrology & Gastroenterology Department, SPH/BMCH, Quetta. One hundred and twenty-five people with cirrhosis participated in the study. Serum creatinine, cystatin C and true GFR by radionuclide scanning were all measured. Creatinine and cystatin C, MDRD and Cockcroft-Gault formulas were used for estimating GFR. The statistical comparisons were made using version 24 of SPSS. Results: The average age among the 125 cirrhotic patients was 56.8, with a variance of 10.2 years. More men (61.6%) than women were part of the study. Compared to measured GFR, the CKD-EPI creatinine-cystatin C formula showed the best correlation (r = 0.82, p < 0.001). Both the MDRD and Cockcroft-Gault equations were found to overestimate GFR by about 11 and 15 mL per minute per square meter (p<0.01). Patients in Child-Pugh class C experienced the greatest difference between the GFR predicted and the GFR measured. Calculations that use Cystatin C gave the best outcomes in patients with more advanced liver disease. Conclusion: For people with cirrhosis, the common eGFR formulas using creatinine may give a misleading assessment of renal function. For patients with kidney disease, especially when creatinine becomes less accurate, use of CKD-EPI that includes cystatin C is the best option.